N-Myc a key gene promoting a worst prostate cancer progression - Di Nunno, Vincenzo; Mollica, Veronica; Massari, Francesco (Translational Cancer Research; Vol 8, No 8 (December 31, 2019): Translational Cancer Research, 2019)
Prostate cancer is a lethal disease and despite several treatments available prognosis of patients with metastatic castration resistant prostate cancer (mCRPC) still remain poor.